A Novel Technique to Detect EGFR Mutations in Lung Cancer - Liu, Yuanbin (Int J Mol Sci, 2016)
Epidermal growth factor receptor (EGFR) gene mutations occur in multiple human cancers; therefore, the detection of EGFR mutations could lead to early cancer diagnosis. This study describes a novel EGFR mutation detection technique. Compared to direct DNA sequencing detection methods, this method is based on allele-specific amplification (ASA), recombinase polymerase amplification (RPA), peptide nucleic acid (PNA), and SYBR Green I (SYBR), referred to as the AS-RPA-PNA-SYBR (ARPS) system. The principle of this technique is based on three continuous steps: ASA or ASA combined with PNA to prevent non-target sequence amplification (even single nucleotide polymorphisms, SNPs), the rapid amplification advantage of RPA, and appropriate SYBR Green I detection (the samples harboring EGFR mutations show a green signal). Using this method, the EGFR 19Del(2) mutation was detected in 5 min, while the EGFR L858R mutation was detected in 10 min. In this study, the detection of EGFR mutations in clinical samples using the ARPS system was compatible with that determined by polymerase chain reaction (PCR) and DNA sequencing methods. Thus, this newly developed methodology that uses the ARPS system with appropriate primer sets is a rapid, reliable, and practical way to assess EGFR mutations in clinical samples.